2018
DOI: 10.1097/htr.0000000000000385
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Symptoms and Objectively Measured Balance Performance Among OEF/OIF Veterans With Remote Mild Traumatic Brain Injury

Abstract: Impaired balance was identified among the cohort. Findings suggest that dizziness, fatigue, depression and PTSD, and time since most recent mTBI may influence balance performance. Additional research is needed to identify the potentially interrelated natural histories of these co-occurring symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Similarly, vestibular impairment with persistent symptoms is well known to occur after concussion; as with multiple sclerosis, peripheral and central aetiology is expected [35]. Moreover, similar relationships between fatigue, dizziness and balance performance have been observed in multiple sclerosis [2,7,8] and concussion patients [36]. Previous research in this patient group has concluded that vestibular rehabilitation is an effective and emerging therapy for managing dizziness, vertigo and imbalance [35,37].…”
Section: Discussionmentioning
confidence: 57%
“…Similarly, vestibular impairment with persistent symptoms is well known to occur after concussion; as with multiple sclerosis, peripheral and central aetiology is expected [35]. Moreover, similar relationships between fatigue, dizziness and balance performance have been observed in multiple sclerosis [2,7,8] and concussion patients [36]. Previous research in this patient group has concluded that vestibular rehabilitation is an effective and emerging therapy for managing dizziness, vertigo and imbalance [35,37].…”
Section: Discussionmentioning
confidence: 57%
“…eight times more likely to have serious difficulty concentrating or remembering, four times more likely to have limitations on daily living, and three times more likely to suffer from depression, anxiety or panic disorder. 18 Veterans who show balance impairment, either via questionnaire 19 or vestibulography 20 are also much more likely to report PTSD symptoms, a finding that may derive from the shared neurochemical features of the ascending vestibular afference and limbic and arousal systems. 21 This same network has also been implicated in the strong association between balance impairment and migraine headache.…”
Section: Pagementioning
confidence: 99%
“…Although many symptoms of mTBIs often subside, there are frequent reports of persistent sequelae following a TBI such as dizziness, imbalance, and vertigo due to deficits in the vestibular system, which integrates multisensory information and is vulnerable to TBIs. These symptoms can result in acute and/or chronic functional limitations that can affect return to duty and unit readiness [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Short- and long-term consequences following a TBI that result in vestibular dysfunction were previously studied using various performance-based measures for balance and self-reported symptom severity and functional limitations [ 7 , 8 ]. Performance-based balance measures have been developed to objectively capture symptom burden for TBIs; however, balance measurement tools such as Functional Gait Assessment and Computerized Dynamic Posturography may lack the sensitivity to capture instability in high-functioning populations such as military SMs or collegiate athletes [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation